Digital livestock systems and probiotic mixtures can improve the growth performance of swine by enhancing immune function, cecal bacteria, short-chain fatty acid, and nutrient digestibility - Park, Sang-O; Seo, Kyung-Hoon (Frontiers in Veterinary Science, 2023)
Digital livestock system and probiotic mixture as technological strategies to improve animal health and production in response to climate change are driving new innovations in the farm animal industry. However, there is little information about effects of a digital livestock system and probiotic mixture (Bacillus subtillus, Streptomyces galilaeus and Sphingobacteriaceae) on growth performance of growth-finishing swine. Thus, the objective of this study was to investigate effects of digital livestock system and probiotic mixture on immune function, cecal bacteria, short chain fatty, nutrient digestibility, and growth performance of growing-finishing swine. A total of 64 crossbred male swine (Duroc × Landrace × Yorkshire, average body weight: 60.17 ± 1.25 kg) were randomly assigned into four treatment groups: CON (control group with a conventional livestock system without probiotic mixture), CON0.4 (conventional livestock system with 0.4% probiotic mixture), DLSC (digital livestock system without probiotic mixture) and DLS0.4 (digital livestock system with 0.4% probiotic mixture). Animals were reared until average body weights reached up to 110 kg under the same standard environmental conditions. Results indicated that growth performance of swine were improved by enhancing nutrient digestibility, and also immune function via modulating blood immune markers in the group with a digital livestock system compared to that the CON, although growth performances of swine were similar between DLSC and CON0.4 groups. Moreover, application of the digital livestock system and a probiotic mixture were maintained higher levels of Lactobacillus, and also balanced short chain fatty acid profiles compared to CON. These results suggest that a digital livestock system and a probiotic mixture can be improved the growth performance of swine by enhancing their nutrient digestibility, improving their immune function, and maintain balanced cecal bacteria and short chain fatty acids. Overall, this study provides insights on the application of a digital livestock system and probiotic mixture as a climate change response strategy to improve swine production.